2021
DOI: 10.1007/s00056-021-00294-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the facial soft tissue profile after maxillary orthognathic surgery

Abstract: Objectives To compare the changes of the soft tissue profile in relation to the displacement of the underlying hard structures in maxillary orthognathic surgery and to contribute to the esthetic prediction of the facial profile after surgical procedures. Materials and methods We analyzed the sagittal changes in the facial soft tissue profile related to surgical changes in skeletal structures after maxillary osteotomy in a retrospective study. The study sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…For those predicted to have an undesirable posttreatment facial profile, orthodontic-orthognathic treatment is preferred over camouflage extraction treatment. At present, prediction of posttreatment facial profile esthetics is mainly performed for orthognathic surgery patients [ 36 38 ]. To the best of our knowledge, this is the first study to predict the posttreatment facial profile esthetics of skeletal Class II extraction patients using a machine-learning method.…”
Section: Discussionmentioning
confidence: 99%
“…For those predicted to have an undesirable posttreatment facial profile, orthodontic-orthognathic treatment is preferred over camouflage extraction treatment. At present, prediction of posttreatment facial profile esthetics is mainly performed for orthognathic surgery patients [ 36 38 ]. To the best of our knowledge, this is the first study to predict the posttreatment facial profile esthetics of skeletal Class II extraction patients using a machine-learning method.…”
Section: Discussionmentioning
confidence: 99%
“…Використання краніометричних точок, як загальновизнаних орієнтирів для проведення досліджень, завжди було «золотим» стандартом, але, з розвитком сучасних методів інструментальних досліджень, коли стало можливим, отримати прижиттєву краніометричну характеристику черепа людини, надало поштовх для вивчення краніології на новому рівні і поставило нові завдання для дослідників [7][8]. Крім цього, постійна модернізація хірургічних маніпуляцій обличчя, потребує уточнення та деталізації морфологічної характеристики шуканої ділянки [9][10].…”
Section: краніометрична характеристика шестикутника обличчя людини зр...unclassified
“…Dentofacial deformity is a morphological anomaly of the maxilla and mandible and is related to different levels of functional alterations. Subjects with dentofacial deformity with retrognathism or prognathism show sagittal maxillomandibular deficiency that affects function and esthetics [5,6]. Recent studies have shown that the size of the mandibular condyle is associated with the morphology of the mandible and the type of facial deformity, indicating that subjects with a smaller mandible have smaller condyles and subjects with facial deformity due to mandibular progeny have larger condyles [7].…”
Section: Introductionmentioning
confidence: 99%